1999
DOI: 10.1136/ebn.2.4.118
|View full text |Cite
|
Sign up to set email alerts
|

Group plus individual education improved quality of life and lung function in patients with asthma

Abstract: Quality of life assessment after patient education in a randomized controlled study on asthma and chronic obstructive pulmonary disease. Am J Respir Crit Care Med 1999 Mar;159:812-7. QuestionDoes an education programme improve health related quality of life and lung function in patients with mild to moderate asthma or chronic obstructive pulmonary disease (COPD)? DesignRandomised, single blind (blinded assessment of spirometry results), controlled trial with follow up at 12 months. SettingAn outpatient che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Margareta, Anna, Mikael, and Christer (2009) showed that educational interventions by asthma nurses did effectively reduce the number of emergency department visits for asthma attacks by asthma patients. This randomized study of patients with asthma (N = 140) aged 18Y70 years showed that educated patients improved their health-related quality of life (HRQOL) scores compared with those who had not received tailored asthma education (Harper, & Wizowski, 1999). Patients whose intensive outpatient treatment also included an educational component had fewer readmissions during the following year (Scullion, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Margareta, Anna, Mikael, and Christer (2009) showed that educational interventions by asthma nurses did effectively reduce the number of emergency department visits for asthma attacks by asthma patients. This randomized study of patients with asthma (N = 140) aged 18Y70 years showed that educated patients improved their health-related quality of life (HRQOL) scores compared with those who had not received tailored asthma education (Harper, & Wizowski, 1999). Patients whose intensive outpatient treatment also included an educational component had fewer readmissions during the following year (Scullion, 2004).…”
Section: Introductionmentioning
confidence: 98%